complemento da outra aqui
Anexos:
![](https://pt-static.z-dn.net/files/d43/db04fee2df33436832b16eabb3e0939e.jpg)
6Pedroca6:
Vejamos...
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
2x -y = 26
• põe X em evidência
X=-2-y
• substitui X
2(-2-y)-y=26
-4-3y=26
-3y=30
Y= -1
Substitui Y
X-10=-2
X=8
X= 8 , y = -10
-x-4y=-1
• põe em evidência X
X= -2-7y
• substitui x
-(-2-7y)-4y=-1
3y=-3
Y= -1
X= 5, Y= -1
Respondido por
1
Aí esta amigão, Espero ter ajudado!
Anexos:
![](https://pt-static.z-dn.net/files/d0a/6cc0e4fd51ad1ae8baf63aedc79e4f5c.jpeg)
B) X= 5 , Y = -1
2x -y = 26
• põe X em evidência
X=-2-y
• substitui X
2(-2-y)-y=26
-4-3y=26
-3y=30
Y= -1
Substitui Y
X-10=-2
X=8
X= 8 , y = -10
-x-4y=-1
• põe em evidência X
X= -2-7y
• substitui x
-(-2-7y)-4y=-1
3y=-3
Y= -1
X= 5, Y= -1
Perguntas interessantes
Geografia,
8 meses atrás
Geografia,
8 meses atrás
Biologia,
8 meses atrás
Matemática,
9 meses atrás
Ed. Física,
9 meses atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás